2018
DOI: 10.1016/j.steroids.2017.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Glycoprotein Non-Metastatic Melanoma Protein B (GPNMB) and Cancer: A Novel Potential Therapeutic Target

Abstract: Glycoprotein non-metastatic melanoma protein B (GPNMB) is a transmembrane protein enriched on the cell surface of cancer cells, including melanoma, glioblastoma, and triple-negative breast cancer. There is growing evidence identifying GPNMB as a tumor-promoter; however, despite its biological and clinical significance, the molecular mechanisms engaged by GPNMB to promote tumorigenesis are not well understood. GPNMB promotes aggressive behaviors such as tumor cell proliferation, migration, and invasion. The ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
86
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(89 citation statements)
references
References 50 publications
2
86
0
1
Order By: Relevance
“…CDX-011 (glembatumumab vedotin) is an antibody-drug conjugate that contains CR011, a human mAb against GPNMB, and conjugates with a cytotoxic agent (MMAE). CDX-011 has been developed for the treatment of GPNMB-expressing cancers, and clinical studies of CDX-011 against patients with breast cancer and melanoma were conducted (12,13,50). We have shown that the cell surface-GPNMB high cells have higher stem cell-like properties than do the cell surface-GPNMB low cells (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…CDX-011 (glembatumumab vedotin) is an antibody-drug conjugate that contains CR011, a human mAb against GPNMB, and conjugates with a cytotoxic agent (MMAE). CDX-011 has been developed for the treatment of GPNMB-expressing cancers, and clinical studies of CDX-011 against patients with breast cancer and melanoma were conducted (12,13,50). We have shown that the cell surface-GPNMB high cells have higher stem cell-like properties than do the cell surface-GPNMB low cells (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…Glycoprotein NMB is a type IA transmembrane protein that is highly expressed in many types of cancers, including melanoma, glioblastoma, and breast cancer. It is considered a poor prognostic factor in those cancers and it might be an attractive therapeutic target …”
Section: Introductionmentioning
confidence: 66%
“…Glembatumumab vedotin, or CDX‐011, an Ab against GPNMB conjugated with an anticancer drug, has been developed to treat GPNMB‐expressing cancers and is in clinical trials for breast cancer and melanoma patients . This suggests the potential of GPNMB as a therapeutic target.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations